Constant low-permeability iron-based magnetic core and preparation method thereof

By combining force field and magnetic field heat treatment, the grain size and magnetic anisotropy of the iron-based magnetic core are regulated, and the problem of excessive permeability of the existing iron-based nanocrystalline magnetic core at low frequency is solved, and the magnetic permeability of the existing iron-based nanocrystalline magnetic core is achieved at 1-100kHz Low and constant magnetic permeability, suitable for applications such as inductors and high current power devices.

CN119252643APending Publication Date: 2025-01-03FOSHAN CITY ZHONGYAN AMORPHOUS TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411588568.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing iron-based nanocrystalline magnetic core has too high permeability and is unstable at 1-100KHz, so it cannot achieve constant permeability characteristics at low frequencies, limiting its use in specific application scenarios such as inductors and high current power devices.

Method used

By performing force-field heat treatment of specific temperature and pressure on the iron-based amorphous magnetic core, combined with magnetic field heat treatment, the grain size, orientation and magnetic anisotropy are regulated, and the permeability of 100-1499 is achieved at 1-100kHz.

Benefits of technology

The low and constant permeability of the iron-based core at 1-100kHz is achieved, which widens its application scenarios, especially in applications of inductors and high current power devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252643A_ABST
    Figure CN119252643A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of magnetic materials, and particularly discloses a constant low-magnetic-conductance iron-based magnetic core and a preparation method and application thereof. The iron-based amorphous magnetic core is sequentially subjected to force field heat treatment and magnetic field heat treatment at the specific temperature and pressure, the iron-based magnetic core with the low magnetic conductivity can be obtained, and the iron-based magnetic core has the characteristic that the magnetic conductivity is smaller than 1500 and is constant at the frequency of 1-100 kHz.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of magnetic materials, and in particular relates to an iron-based magnetic core with constant low magnetic permeability and a preparation method and application thereof. Background Art

[0002] Iron-based amorphous / nanocrystalline soft magnetic alloys are usually made of amorphous strips by high-speed copper roller rapid cooling process from master alloys, and the amorphous strips are wound into amorphous magnetic cores. Amorphous magnetic cores generally need to undergo appropriate heat treatment processes to finely control the microstructure of the alloy, that is, a single magnetic α-Fe phase is precipitated on the amorphous matrix to transform into a two-phase coexistence structure of amorphous and nanocrystalline to form a nanocrystalline magnetic core. This special two-phase nanostructure is also the main reason why the nanocrystalline magnetic core exhibits excellent comprehensive soft magnetic properties. Therefore, the heat treatment process of the magnetic core plays a decisive role in obtaining high-performance iron-based magnetic cores. However, the heat treatment process in the prior art generally makes the obtained nanocrystalline magnetic core often show the characteristics of high magnetic permeability and greatly reduced with the increase of frequency. At 1-100KHz, the magnetic permeability is too high and unstable, and it is impossible to achieve the characteristics of constant and low magnetic permeability of the magnetic core at low frequency. It cannot be used in specific application scenarios such as inductors and high-current power devices that require a magnetic permeability below 1500 at 1-100KHz, which limits its application.

[0003] Therefore, it is urgent to develop a process for preparing a magnetic core to achieve a magnetic core with a magnetic permeability below 1500 at 1-100 KHz. Summary of the invention

[0004] In view of the problem in the prior art that it is difficult to obtain a magnetic core with low and constant magnetic permeability, the present invention provides an iron-based magnetic core with constant low magnetic permeability and a preparation method thereof.

[0005] To achieve the above purpose, the following technical solutions are specifically included:

[0006] A method for preparing an iron-based magnetic core comprises the following steps:

[0007] (1) heating the iron-based amorphous magnetic core to a preset temperature and pressurizing it to a preset pressure, and then cooling it to below 200° C. and releasing the pressure to obtain a pre-burned magnetic core; the preset temperature is 300-425° C., and the preset pressure is 60-150 MPa;

[0008] (2) The pre-burned magnetic core is subjected to a magnetic field heat treatment and, after cooling, an iron-based magnetic core is obtained.

[0009] In the method of the present invention, the iron-based amorphous magnetic core is subjected to force field heat treatment and magnetic field heat treatment at specific temperature and pressure in sequence to control the grain size, grain orientation, and magnetic anisotropy, so that the iron-based magnetic core has an effective magnetic permeability of 100-1499 at a frequency of 1-100kHz, thereby broadening the application scenarios of the iron-based magnetic core.

[0010] Under the force field heat treatment, on the one hand, the pressure promotes the precipitation of nano-crystals but at the same time inhibits the rapid growth of nano-crystals. To a certain extent, by controlling the grain size, the magnetic core is kept at a relatively low magnetic permeability and a relatively stable magnetic permeability; on the other hand, the existence of the pressure field can induce magnetic anisotropy inside the magnetic core, increase the domain wall energy, and the high domain wall energy prevents the movement of the domain wall. To a certain extent, by regulating the domain wall energy, the magnetic permeability of the magnetic core is relatively low and the magnetic permeability is relatively stable. The inventors of the present invention have found that the temperature and pressure of the force field heat treatment have a significant effect on the magnetic permeability and its stability. Under the force field heat treatment of 300-425℃, the magnetic core can still maintain a relatively low magnetic permeability and a relatively stable magnetic permeability. However, if it deviates slightly from the above temperature range, the temperature is too high, which will cause the magnetic permeability to be too large and the magnetic permeability stability to drop sharply. Although the magnetic permeability meets the requirements at low temperatures, its magnetic permeability stability will still drop sharply and does not meet the requirements. Under the force field pressure of 60-150MPa, the magnetic core can maintain a relatively low magnetic permeability and a relatively stable magnetic permeability. However, when slightly deviated from the above pressure range, although the magnetic permeability of the magnetic core meets the requirements, the stability of the magnetic permeability cannot meet the requirements. Therefore, the thermal force field of the present invention is actually a heat treatment method through rapid heating and rapid cooling. Under the synergistic effect of specific temperature and high pressure, it promotes the continuous precipitation of nano-crystals while inhibiting the growth of nano-crystals, controls the state and size of the grains in the magnetic core, and improves the domain wall energy to a certain extent, thereby achieving the overall performance effect of low magnetic permeability and constant magnetic permeability of the magnetic core. The actual effect of magnetic field heat treatment is to induce grain orientation growth, that is, to promote the orientation of nano-crystals along the direction of magnetic field application, thereby inducing magnetic anisotropy and regulating the shape of hysteresis loop. The force field heat treatment and the magnetic field heat treatment cooperate with each other. It is necessary to regulate the grain and domain wall energy by force field heat treatment, and then regulate the oriented growth of grains by magnetic field heat treatment. If there is any lack of the condition of applying a pressure greater than atmospheric pressure or a constant magnetic field, the obtained magnetic core cannot maintain the performance of low frequency and low constant magnetic permeability, and cannot achieve the performance requirement of the present invention of an effective magnetic permeability of 100-1499 at a frequency of 1-100kHz.

[0011] Preferably, in step (1), the iron-based amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%.

[0012] Further preferably, the iron-based amorphous magnetic core comprises Fe 73.5 Si 15.5 B7Cu1Nb3、Fe 73.5 Si 13.5 B9Cu1Nb3、Fe 63.5 Ni 10 Si 15.5 B7Cu1Nb3、Fe 63.5 Co5Ni5Si 15.5 B7Cu1Nb3、Fe 68.5 Co5Si 15.5 At least one of B7Cu1Nb3.

[0013] The method of the present invention is actually a heat treatment method, which is effective for a variety of iron-based alloys and adaptable to different types of amorphous magnetic cores, and is particularly suitable for iron-based amorphous magnetic cores within the above-mentioned element content range, so that the magnetic core made from the above-mentioned iron-based amorphous magnetic core has an effective magnetic permeability of less than 1500 at 1-100KHz.

[0014] Preferably, in step (1), the heating rate when the iron-based amorphous magnetic core is heated to a preset temperature is 5-30° C. / min.

[0015] The heating rate affects the time it takes for the iron-based amorphous magnetic core to be heated to the preset temperature. The greater the heating rate, the shorter the required heating time, and the faster the preset temperature of the heat treatment can be reached, which prevents the grains in the magnetic core from growing too large during the heating process and making it impossible to effectively control the magnetic permeability and its stability. At the above heating rate, the magnetic core can have an effective magnetic permeability of less than 1500 at 1-100KHz.

[0016] Preferably, in step (1), the cooling rate is 50-1000° C. / min.

[0017] After reaching the preset temperature and pressure, the core begins to cool down. The temperature rate of natural furnace cooling is generally 6-8℃ / min. Cooling rates greater than this range require auxiliary rapid quenching equipment. The cooling rate within the above range belongs to rapid quenching, which can quickly cool the core and shorten the time the core stays at a high temperature, avoiding excessive growth of grains in the core and effectively controlling the size of recrystallized grains, so that the final core maintains a lower magnetic permeability and higher stability.

[0018] Preferably, the pressurization method includes at least one of inert gas pressure pressurization and mold extrusion pressurization. Further preferably, the inert gas includes at least one of argon and nitrogen.

[0019] Preferably, the temperature of the magnetic field heat treatment is 300-380° C., and the magnetic field intensity of the magnetic field heat treatment is 800-3000 Gs.

[0020] Preferably, the magnetic field heat treatment lasts for 1-120 min, more preferably 30-60 min.

[0021] The higher the magnetic field intensity, the higher the heat treatment temperature, and the longer the holding time, the greater the degree of induced grain orientation growth, the lower the magnetic permeability, and the higher the magnetic permeability stability. However, the higher the magnetic field intensity, the higher the heat treatment temperature, and the longer the holding time, not only significantly increase the actual production cycle, cost, and equipment loss, but also the degree of induced grain orientation growth by magnetic field heat treatment will decrease, and long-term high-temperature growth will lead to excessive growth of nano-grains, resulting in increased magnetic permeability and decreased magnetic permeability stability. Therefore, under the magnetic field heat treatment conditions in the above range, the purpose of maintaining a lower magnetic permeability and higher stability of the magnetic core of the present invention can be achieved.

[0022] Preferably, the iron-based amorphous magnetic core in step (1) is formed by winding an iron-based amorphous strip.

[0023] Preferably, the direction of the magnetic field in the magnetic field heat treatment in step (2) is parallel to the width direction of the iron-based amorphous strip.

[0024] Preferably, in step (2), the cooling is natural cooling.

[0025] Preferably, the magnetic permeability of the iron-based magnetic core is constant at a frequency of 1-100 kHz, and the magnetic permeability of the iron-based magnetic core is 1500-14999; the iron-based magnetic core contains an amorphous phase and nano-sized grains.

[0026] Further preferably, when the magnetic permeability of the iron-based magnetic core is constant, the change rate of the effective magnetic permeability of the iron-based magnetic core at a frequency of 1-100 kHz is ≤5%.

[0027] The present invention also provides an application of the iron-based magnetic core in preparing an inductor and a high-current power device.

[0028] Compared with the prior art, the present invention has the following beneficial effects: the present invention can obtain an iron-based magnetic core with low magnetic permeability by subjecting the iron-based amorphous magnetic core to force field heat treatment and magnetic field heat treatment at specific temperature and pressure in sequence, and the iron-based magnetic core has the characteristic of a constant magnetic permeability of less than 1500 at 1-100kHz. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the X-ray diffraction (XRD) pattern of the homemade amorphous ribbon.

[0030] Figure 2This is a physical picture of the magnetic core prepared in Example 1.

[0031] Figure 3 A comparison diagram of the magnetic domain structures between Example 1 (left) and Comparative Example 3 (right).

[0032] Figure 4 Graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of Examples 1 to 16.

[0033] Figure 5 This is a graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of comparative examples 1 to 7. DETAILED DESCRIPTION

[0034] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.

[0035] The amorphous strips used in the following embodiments and comparative examples can be purchased from the market or prepared by conventional methods. The methods may include the following steps: (1) component proportioning; (2) master alloy smelting; and (3) obtaining the corresponding amorphous strips by strip spinning and strip winding.

[0036] Example 1

[0037] A method for preparing an iron-based magnetic core comprises the following steps:

[0038] (1) The alloy Fe in atomic percentage 73.5 Si 15.5 B7Cu1Nb3 amorphous strip (self-made, its XRD results are shown in the attached Figure 1 ) is wound into an amorphous magnetic core, and then the amorphous magnetic core is placed in a furnace body, evacuated, filled with inert gas argon gas, so that there is a certain pressure in the system, and heated to a force field heat treatment temperature of 350°C at a heating rate of 15°C / min, and at the same time, argon gas is continuously filled to pressurize to a preset pressure of 130MPa; then, cooled at a cooling rate of 100°C / min, and the pressure is released after cooling to below 200°C until room temperature and normal pressure are obtained.

[0039] (2) The pre-burned magnetic core is placed in the magnetic field heat treatment furnace and heated to a magnetic field heat treatment temperature of 350°C at a heating rate of 10°C / min. At this time, a magnetic field parallel to the width direction of the magnetic core is applied, and the core is kept warm for 60 minutes under a magnetic field strength of 1000Gs. The core is cooled to room temperature along with the furnace to obtain an iron-based magnetic core.

[0040] Examples 2-15 and Comparative Examples 1-7

[0041] The only difference between Examples 2-15 and Comparative Examples 1-7 and Example 1 is: in steps (1)-(2), the heating and cooling rates, force field heat treatment temperature, preset pressure, magnetic field intensity, magnetic field heat treatment temperature or holding time. See Table 1 for detailed differences.

[0042] Example 16

[0043] The difference between this embodiment 1 and the embodiment is that the alloy of this embodiment is Fe in atomic percentage. 73.5 Si 13.5 B9Cu1Nb3 amorphous strip, the amorphous strip is obtained in the same way as the amorphous strip of Example 1, and can be obtained by commercial methods or by conventional methods. The homemade methods of this embodiment and Example 1 may include the following processes: (1) component ratio; (2) master alloy smelting; (3) obtaining the corresponding amorphous strip through strip spinning and strip winding.

[0044] Table 1

[0045]

[0046]

[0047] The iron-based magnetic cores prepared in the above embodiments and comparative examples were tested for performance: the inductance L of the magnetic core was tested using a Keysight Agilent 4294A precision impedance analyzer in an applied magnetic field of 1A / m and a frequency range of 1kHz to 100kHz; the effective magnetic permeability μ e Obtained through the inductance L conversion formula:

[0048] μ e =(L×L e ) / (N 2 ×A e ),

[0049] Where, L is the core inductance, μ e is the effective magnetic permeability of the core, L e is the magnetic path length of the core, A e is the effective cross-sectional area of ​​the core, and N is the number of coil turns (the test condition is 1 turn).

[0050] μ e Change rate % calculation method: μ e Change rate % = (μ e(1kHz) -μ e(100kHz) ) / μ e(1kHz) ×100%, μ e A rate of change less than 5% is considered constant permeability.

[0051] Table 2

[0052]

[0053]

[0054] Combined with Table 2 and Appendix Figure 2 , 4 -5 analysis, it can be seen from Examples 1-16 and Comparative Examples 1-7 that the present invention combines force field and magnetic field heat treatment with each other, and requires heat treatment at specific temperature and pressure, which can enable the iron-based magnetic core to have a low, stable or constant effective magnetic permeability at 1-100KHz, and the effective magnetic permeability is in the range of 100-1499.

[0055] In the method of the present invention, under the force field heat treatment, the rate of temperature rise / fall, heat treatment temperature, holding time, and pressure can have a certain influence on the magnetic permeability and magnetic permeability stability of the iron-based nanocrystalline magnetic core. This is because: on the one hand, the pressure promotes the precipitation of nanocrystal grains but at the same time inhibits the rapid growth of nanocrystal grains, and to a certain extent, the magnetic core is kept at a relatively low magnetic permeability and a relatively stable magnetic permeability by controlling the grain size; on the other hand, the existence of the pressure field can induce magnetic anisotropy inside the magnetic core, increase the domain wall energy, and the high domain wall energy prevents the movement of the magnetic domain wall, and to a certain extent, the magnetic permeability of the magnetic core is relatively low and the magnetic permeability is relatively stable by regulating the magnetic domain wall energy. The goal of the present invention is to achieve a constant effective magnetic permeability of 100-1499 at 1-100KHz to achieve the purpose of application in specific fields. It can be observed from the above-mentioned embodiments 1-3, 8-9, and 16 that under the thermal force field, the heating rate can be selected as 5-30℃ / min, the cooling rate can be selected as 50-1000℃ / min, and different types of amorphous magnetic cores can be selected, and the magnetic properties required by the present invention can be achieved within a relatively wide range. The above-mentioned heating rate and cooling rate belong to the degree of rapid heating and rapid cooling in the field of industrial production, shortening the time of the magnetic core in the heat treatment process, avoiding excessive growth of the grains in the magnetic core, resulting in unqualified magnetic permeability and stability, especially in the cooling process, the temperature rate of natural furnace cooling is generally 6-8℃ / min, and the cooling rate greater than this range requires auxiliary rapid quenching equipment to achieve. From embodiments 1, 4-7 and comparative examples 1, 4-7, it can be seen that the temperature and pressure of the force field heat treatment have a very significant effect on the magnetic permeability and stability. Under the force field heat treatment of 300-425℃, the magnetic core can still maintain a relatively low magnetic permeability and a relatively stable magnetic permeability. However, if it deviates slightly from the above temperature range, the temperature is too high, which will lead to excessive magnetic permeability and a sharp drop in magnetic permeability stability. Although the magnetic permeability meets the requirements when the temperature is low, its magnetic permeability stability will still drop sharply and does not meet the requirements. Under the force field pressure of 60-150MPa, the magnetic core can maintain a relatively low magnetic permeability and a relatively stable magnetic permeability. However, if it deviates slightly from the above pressure range, although the magnetic permeability of the magnetic core meets the requirements, the stability of the magnetic permeability cannot meet the requirements. Therefore, the thermal force field of the present invention is actually a heat treatment method of rapid heating and rapid cooling. Under the synergistic effect of specific temperature and high pressure, it promotes the continuous precipitation of nano-crystals while inhibiting the growth of nano-crystals, controls the grain state and size in the magnetic core, improves the domain wall energy to a certain extent, and achieves the performance effect of low magnetic permeability and constant magnetic permeability of the magnetic core as a whole.

[0056] Under magnetic field heat treatment, magnetic field intensity, holding time and heat treatment temperature can have a certain impact on the magnetic permeability and stability of iron-based nanocrystalline cores. This is because the actual effect of magnetic field heat treatment is to induce grain orientation growth, that is, to induce the orientation of nanocrystalline grains along the direction of magnetic field application, thereby inducing magnetic anisotropy and regulating the shape of hysteresis loop. It can be seen from the above embodiments 1 and 10-15 that the magnetic field heat treatment temperature is 300-380°C, the magnetic field strength is 800-3000Gs, and the holding time is 30-120min. The higher the magnetic field strength, the higher the heat treatment temperature, and the longer the holding time, the greater the degree of induced grain orientation growth, the lower the magnetic permeability, and the higher the magnetic permeability stability. However, the higher the magnetic field strength, the higher the heat treatment temperature, and the longer the holding time not only significantly increase the actual production cycle, cost, and equipment loss, but also the degree of induced grain orientation growth by magnetic field heat treatment will decrease, and long-term high-temperature growth will lead to excessive growth of nano-grains, resulting in an increase in magnetic permeability and a decrease in the stability of magnetic permeability. Therefore, the conditions for magnetic field heat treatment in the present invention are preferably within the following parameter ranges: the magnetic field heat treatment temperature is 300-380°C, the magnetic field strength is 800-3000Gs, and the holding time is 30-120min.

[0057] It can be seen from Example 1 and Comparative Examples 1-3 that force field heat treatment and magnetic field heat treatment cooperate with each other. It is necessary to regulate the grains and domain wall energy by force field heat treatment, and then regulate the oriented growth of grains by magnetic field heat treatment. If there is any lack of conditions of applying a pressure greater than atmospheric pressure or a constant magnetic field, the magnetic core obtained cannot maintain the performance of low frequency and low constant magnetic permeability.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an iron-based magnetic core, characterized in that: The steps include: (1) heating the iron-based amorphous magnetic core to a preset temperature and pressurizing it to a preset pressure, and then cooling it to below 200° C. and releasing the pressure to obtain a pre-burned magnetic core; the preset temperature is 300-425° C., and the preset pressure is 60-150 MPa; (2) The pre-burned magnetic core is subjected to a magnetic field heat treatment and, after cooling, an iron-based magnetic core is obtained.

2. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: In step (1), the heating rate when the iron-based amorphous magnetic core is heated to a preset temperature is 5-30°C / min.

3. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: In step (1), the cooling rate is 50-1000°C / min; the pressurization method includes at least one of gas pressure pressurization and mold extrusion pressurization.

4. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: In step (2), the temperature of the magnetic field heat treatment is 300-380°C, and the magnetic field intensity of the magnetic field heat treatment is 800-3000Gs.

5. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: In step (2), the time of the magnetic field heat treatment is 1-120 min, and the cooling is natural cooling.

6. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: The iron-based amorphous magnetic core described in step (1) is formed by winding an iron-based amorphous strip, and the magnetic field direction of the magnetic field heat treatment described in step (2) is parallel to the width direction of the iron-based amorphous strip.

7. The method for preparing an iron-based magnetic core according to claim 1, characterized in that: In step (1), the iron-based amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%.

8. An iron-based magnetic core obtained by the method for preparing an iron-based magnetic core according to any one of claims 1 to 7.

9. The iron-based magnetic core according to claim 8, characterized in that: The magnetic permeability of the iron-based magnetic core is constant at a frequency of 1-100kHz, and the magnetic permeability of the iron-based magnetic core is 100-1499; the iron-based magnetic core contains an amorphous phase and nano-sized grains.

10. Use of the iron-based magnetic core according to claim 8 or 9 in the preparation of inductors and high-current power devices.

Citation Information

Cited By

  • Iron-based magnetic core with constant low magnetic permeability and preparation method therefor

    WO2026097698A1